Evaluation of Serum C-Reactive Protein, Plasma Fibrinogen, and Blood Leukocytes in Patients with Chronic Periodontitis - Kafle, Shristi; Shrestha, Erika; Yadav, Sanjay (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Introduction: Periodontal health is crucial and indispensable element of general health. Epidemiologically, it has been linked with cardiovascular diseases with elevated acute phase reactant C-reactive protein, fibrinogen and rheological variables such as total leukocyte count and differential leukocyte counts, which are potential predictors of cardiovascular diseases. Objective: To evaluate and compare cardiovascular disease-related biochemical markers in periodontally healthy subjects, and patients with moderate and severe chronic periodontitis. Methods: An analytical cross-sectional study was conducted in patients attending Department of Periodontology and Oral Implantology, Chitwan Medical College and Teaching hospital, Bharatpur, Chitwan, Nepal from September 2019 to January 2021. A total of 81 individuals of both gender of which 27 periodontally healthy individuals, 27 diagnosed with moderate and 27 diagnosed with severe periodontitis based on gingival index, probing pocket depth and clinical attachment level were enrolled in a study. After which, peripheral blood samples were drawn and serum C-reactive protein, plasma fibrinogen, total leukocyte count and differential leukocyte counts were quantified using the turbidimetric immunoassay. Convenience sampling technique was done. Data was analysed in SPSS v.26.0. Results: The mean serum levels of C-reactive protein, plasma fibrinogen, total leukocyte and differential leukocytes were found to be statistically (P value <0.001) higher in severe and moderate periodontitis subjects compared to periodontally healthy subjects. Conclusion: The increased levels of serum C-reactive protein, plasma fibrinogen, total leukocyte count, and differential leukocyte counts in chronic periodontitis contribute to the inflammatory burden of the individual potentially striking toward an increasing risk for cardiovascular events.